Radiation Pattern Performance of Unequally Linear Arrays with Parasitic Element - Noor Ainniesafina Zainal; Muhammad Ramlee Kamarudin; Yoshihide Yamada; Norhudah Seman (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
For next generation of 5G mobile base station antennas, multibeam, multifrequency and low sidelobe characteristics requested. Simplify the feeding network will contribute a low feeder loss and frequency dependent. From the previous research by the author, low sidelobe level reported by density tapered array configuration from -13 dB to -16 dB and the result maintained for wideband operation frequency at 28 GHz, 42 GHz, and 56 GHz. However, the grating lobe has occurred due to element spacing larger than a wavelength of higher frequency (56 GHz). In this paper, an investigation was made of the performance of radiation pattern for unequally microstrip linear array antenna in frequency 42 GHz and 56 GHz by loading parasitic elements. The effect of parasitic element to the impedance, gain, and sidelobe level of unequally microstrip linear spaced tapered array also examined. The design has been simulated using Ansoft High Frequency Structural Simulator (HFSS) ver 16.0.